Global and local hydrodynamics of bubble columns: effect of gas distributor - Sharaf, Safa; Zednikova, Maria; Ruzicka, Marek C.; Azzopardi, Barry J. (Elsevier, 2016)
Global (level swell) and local (WMS – Wire Mesh Sensor) measurements were made on waters of different purities and air, in a cylindrical laboratory bubble column (2 m tall, 0.127 m dia) using two different gas distributors: a perforated plate (to produce homogeneous flow) and a spider sparger (to produce heterogeneous flow). The level swell method provided the steady space-averaged gas holdup/gas flow rate data. The WMS method provided the actual gas holdups and bubble sizes resolved in time and space at one cross-sectional horizontal plane (1 m above distributor), whose integration yields the timeaveraged data. The following results were obtained: The global and local data agree relatively well; there are distinct differences between the radial profiles and bubble size distributions between the two main flow regimes; the local information identifies why the predictions of published models, which account for the smaller and larger bubbles in the flow, may not perform well; the modelling approaches based on the hindrance and enhancement concepts prove to be suitable for the flow regime identification and description, including the transition range between the homogeneous and heterogeneous flows; based on the hydrodynamics, the specific interfacial area is obtained, together with the mass transfer coefficient.